UJI DAYA HAMBAT EKSTRAK KULIT BATANG Rhizophora mucronata TERHADAP PERTUMBUHAN BAKTERI Aeromonas hydrophila, Streptococcus agalactiae DAN JAMUR Saprolegnia sp. SECARA IN VITRO - Dedi Pradana; Dwi Suryanto; Yunasfi Djayus (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
This study was aimed to determine antimicrobial potential of stem bark extract of Rhizophora mucronata against bacterial pathogens i.e. Aeromonas hydrophila, Streptococcus agalactiae and fungus Saprolegnia sp. and to determine the extract toxicity to Artemia Salina Leach. Extraction was done by a single maceration using methanol, ethyl acetate and n-hexane. Phytochemical test was conducted to all extracts. Toxicity test was conducted using Brine Shrimp Lethality Test. Antimicrobial activity test was done using the agar diffusion method. Phytochemical test of stem bark extract of Rhizophora mucronata showed that the extract contained of alkaloid, tannin, steroid/terpenoid and saponin. All of the extact of Rhizophora mucronata were toxic to A. salina. The result showed that ethyl acetate extract was the most toxic. Antimicrobial test results showed that ethyl acetate extract of stem bark of R. mucronata was broad antimicrobial spectrum because it was able to inhibit the growth of all microbes.Keywords: Antimicrobial activity, Aeromonas hydrophila, Rhizophora mucronata, Streptococcus agalactiae, Saprolegnia sp.